2022
DOI: 10.1136/gutjnl-2021-325021
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke promotes colorectal cancer through modulation of gut microbiota and related metabolites

Abstract: ObjectiveCigarette smoking is a major risk factor for colorectal cancer (CRC). We aimed to investigate whether cigarette smoke promotes CRC by altering the gut microbiota and related metabolites.DesignAzoxymethane-treated C57BL/6 mice were exposed to cigarette smoke or clean air 2 hours per day for 28 weeks. Shotgun metagenomic sequencing and liquid chromatography mass spectrometry were parallelly performed on mice stools to investigate alterations in microbiota and metabolites. Germ-free mice were transplante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 41 publications
2
98
0
1
Order By: Relevance
“…Carcinogens can stimulate abnormal cell proliferation and EMT, leading to lung cancer ( 10 12 ). TS-induced abnormal EMT and cell proliferation regulate early events in cancer ( 54 56 ). In the present study, the change in the expression levels of EMT and proliferation markers indicated abnormal EMT and cell proliferation in the lungs of mice exposed to TS.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinogens can stimulate abnormal cell proliferation and EMT, leading to lung cancer ( 10 12 ). TS-induced abnormal EMT and cell proliferation regulate early events in cancer ( 54 56 ). In the present study, the change in the expression levels of EMT and proliferation markers indicated abnormal EMT and cell proliferation in the lungs of mice exposed to TS.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is associated with genetic and epigenetic mutations leading to CRC, such as genetic microsatellite instability and mutations in oncogenes and tumor suppressor genes [ 103–105 ]. Gut dysbiosis was reported in CRC in both humans and rodent studies [ 106 , 107 ]. Recent studies suggested that gut microbial dysbiosis during CRC is associated with tumorigenesis, mutagenesis and epigenetic modifications related to CRC [ 108 , 109 ], and may potentially help in CRC detection [ 105 , 106 ].…”
Section: Microbial Dysbiosis In Smoking-associated Diseasesmentioning
confidence: 99%
“…Bai et al [ 107 ] recently showed that mice treated with the carcinogen azoxymethane for CRC induction and exposed to cigarette smoke developed an increased number of colorectal tumors and enhanced proliferation of colonic epithelial cells compared with cancer-induced mice exposed to air. Notably in this study, mice exposed to smoke exhibited gut microbial dysbiosis, which included significant enrichment of Eggerthella lenta and Staphylococcus capitis and reduction in Parabacteroides distasonis and Lactobacillus species.…”
Section: Microbial Dysbiosis In Smoking-associated Diseasesmentioning
confidence: 99%
See 2 more Smart Citations